Perancangan Sistem Air blast freezing Berkapasitas 25 Kg dengan Sistem Refrigerasi Cascade Menggunakan Refrigerant R290/R32 - Martin, Awaludin; Sihombing, Tikkos; Rizqullah, Ibnu; Auliaswan, Fayzil; Mainil, Rahmat Iman (TURBO [Tulisan Riset Berbasis Online], 2025)
Indonesia is a country rich in marine catch, especially shrimp commodities, with a production volume reaching 1.12 million tons, but only 220 thousand tons or approximately 19.64%, are exported. One contributing factor to the low export rate is poor temperature control throughout the cold chain supply process. The aim of this study to design and develop an air blast freezing system with a capacity of 25 kg, and to compare the design results with experimental data. The main focus of the research is to increase the cooling system’s capacity to meet the demands of the cold chain in the storage of marine catch, while maintaining product temperatures consistently between -18 °C and -25 °C. The design results for the low-temperature cycle (LTC) yielded evaporator load of 788.66 W, compressor power of 221.78 W, condenser load of 1317.64 W, and an evaporator surface area of 4.84 m². For the high-temperature cycle (HTC), the evaporator load was 1499.76 W, compressor power was 159.61 W, condenser load was 948.27 W, and condenser surface area was 8.98 m². Experimental tests showed that the system was able to reach product temperatures between -19.6 °C and -25.3 °C, with a design COP of 2.014 and an actual COP of 2.413 for the cascade system